The role of body information in the perception of social attention - Pomianowska, Iwona (Trinity College (Dublin, Ireland). School of Psychology, 2011)
The computation of where another person is attending constitutes a crucial part of our daily lives and is necessary for adequately interacting with other human beings in our social environment. The focus of the present dissertation is on social perception, a term often used to refer to the initial stages in the processing of socially relevant information (e.g., gaze, head and body direction, implied or actual body movements) that culminates in the accurate analysis of the dispositions and intentions of others.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin.